Recognition of Foreign Legal Entities: How a country recognizes the legality of a Corporation established abroad - Saurav Kumar (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2026)
This paper examines the legal mechanisms and principles governing the recognition of foreign legal entities, focusing on how a host country acknowledges the legality and corporate personality of a corporation established abroad. In an increasingly globalized economy, the cross-border operation of multinational corporations hinges on their capacity to exercise legal rights and assume obligations outside their state of incorporation. This study analyzes the primary doctrinal approaches to determining a corporation’s personal law: the Incorporation Doctrine, which looks to the place of registration, and the Real Seat (Siège Réel) Doctrine, which emphasizes the principal place of management. Furthermore, the paper explores the role of international treaties, bilateral investment treaties (BITs), and private international law rules in facilitating or restricting this recognition. By examining potential conflicts of laws and public policy exceptions, this research highlights the balance host states must strike between protecting domestic markets and fostering international commerce. Ultimately, the paper provides a comprehensive legal framework essential for understanding transnational corporate mobility and cross-border commercial litigation.